Sistem Pendukung Keputusan Rekomendasi Penerimaan Bantuan Kartu Indonesia Pintar Dengan Menerapkan Metode Maut Dan Pembobotan Dengan Menggunakan Metode Roc Pada Sekolah Yapim Taruna Medan - Rizka Rahayu Pasaribu; Muhammad Syahrizal; Sumiaty Adelina Hutabarat (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The Smart Indonesia Card is the provision of educational cash assistance to children aged 6-21 years or who come from underprivileged families with the aim of continuing their education. Yapim Taruna Medan High School is one of the private schools in the city of Medan. This school provides Smart Indonesia Card scholarship assistance (KIP) where KIP scholarships are intended for underprivileged students and the number of KIP recipients is also limited based on the quota given, which is faced by the Yapim Taruna Medan High School in determining who is who. those who get KIP scholarships are less objective and transparent. Many students whose parents have a very difficult economy do not get KIP scholarships while some students who get KIP scholarships have parents who are above the economy who do not get the scholarship. So that to overcome this problem a Decision Support System for Recommendations for Accepting Indonesian Smart Card assistance is needed by applying the MAUT Method and Weighting Using the ROC Method at the Medan Yapim Taruna School.